Chinese Students and the Experience of International Doctoral Study in STEM - Song, Siqi (Journal of International Students, 2023)
This book contributes to the field of international higher education through a continuous, interactive, and situative approach in its examination of the experience of Chinese international doctoral students in STEM. It offers an original three-dimensional multi-world framework to conceptualize the complexity of cross-cultural doctoral studies and provides engaging narratives of Chinese doctoral students in STEM in Australian universities. The book will be valuable to faculty supervisors of international doctoral students, university administrators, and researchers interested in student experience in international higher education.